PENGARUH EDUKASI PASIEN BERBASIS VIDEO EDUKASI TERHADAP KEPATUHAN PASIEN DIABETES TIPE 2 DI PUSKESMAS PASAR SIMPANG, LAMPUNG - Bangsawan, Tasya Okta Permata; Ghozali, Muhammad Thesa (As-Syifaa Jurnal Farmasi, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycaemia due to ineffective insulin use. In Indonesia, DM is a leading non-communicable disease. Medication adherence plays a critical role in managing DM, yet barriers such as long treatment regimens and limited patient-provider communication often hinder adherence. This study evaluated the effectiveness of a video-based digital intervention in improving medication adherence among DM patients at Public Health Center of Pasar Simpang in Kota Agung Timur, Tanggamus Regency. The study employed a cross-sectional design with 62 respondents divided into control and experimental groups. The intervention involved educational videos shared via WhatsApp. Adherence was assessed using the MMAS-8 (Morisky Medication Adherence Scale). Results revealed that adherence levels significantly improved in the experimental group post-intervention. The pre-test MMAS-8 mean score was 11.23±1.26, increasing to 13.97±1.33 post-intervention, with a mean difference of 2.74 (p = 0.000). In contrast, the control group showed no significant change, with pre- and post-test mean scores of 12.55±1.55 and 12.90±1.42, respectively (p = 0.315). Overall, 79% of respondents demonstrated good adherence, with significant improvements noted in the intervention group. These findings highlight the potential of video-based digital interventions in enhancing adherence among DM patients, providing valuable insights into diabetes care.